2017
DOI: 10.1007/s10597-017-0100-4
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Partner Support for Lifestyle Change Among Adults with Serious Mental Illness: A Feasibility Pilot Study

Abstract: The purpose of this pilot study was to explore the feasibility of an intervention designed to facilitate partner support for lifestyle change among overweight and obese adults with serious mental illness (SMI). Fifteen adults with SMI enrolled in a lifestyle intervention at community mental health centers participated with a self-selected partner in an additional 12-week intervention component designed to facilitate social support for health behavior change. Participants reported that the program was useful, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…We found behavior change was facilitated by relationships, a finding consistent with studies reporting a link between peer support and positive health outcomes ( Aschbrenner et al, 2016 , 2017 ). Through a qualitative methodology and approach, our findings provide a rich understanding of this association.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found behavior change was facilitated by relationships, a finding consistent with studies reporting a link between peer support and positive health outcomes ( Aschbrenner et al, 2016 , 2017 ). Through a qualitative methodology and approach, our findings provide a rich understanding of this association.…”
Section: Discussionsupporting
confidence: 89%
“…The authors observed a “link between making health behavior changes necessary for weight loss and perceived peer support” and identified that this link was not fully understood; they advocated for future qualitative research to explore the impact of peer support on health behavior change among MHSUs. The same authors identify positive partner support providing encouragement, practical support, and exercising together as supporting outcomes such as readiness to engage in PA and weight loss ( Aschbrenner et al, 2017 ).…”
mentioning
confidence: 99%
“…Although much of the current research on PGD use within the clinical environment has been in the context of physical health treatment such as irritable bowel syndrome [ 16 ], diabetes [ 26 ], and heart failure [ 27 ], there is a growing focus on the role of PGD in mental health treatment. The early work exploring the integration of wearables into mental health treatment largely centered on their use for the adjunctive goal of weight loss [ 28 , 29 ]. The goal of this research was to determine if wearable devices designed to promote PA would be acceptable and feasible in populations in high-risk and challenging populations.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it was found that people with SMI found the devices easy to use and useful for motivation, goal setting, facilitating social connection, and self-monitoring [ 28 ]. Indeed, integrating such devices into a lifestyle intervention for individuals with SMI was found to be able to significantly reduce weight below baseline levels [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…As social support has been found to be a strong predictor of exercise adoption and maintenance,47 this study targets social isolation as a barrier to engagement by providing peer-to-peer support within the Facebook group and including support partners. Previous research has found that carers have the potential to support and extend interventions that are aimed at improving chronic disease risk behaviours of people with mental illness 48. However, there is currently limited information or services available to support family and carers in helping their family members, with carers reporting they often feel disconnected from healthcare professionals 49–51.…”
Section: Discussionmentioning
confidence: 99%